Impacts of heat stress on mineral nutrition of boro rice cultivar (BR 19) as influenced by the indigenous organic fertilizers - Hossain, Mohammed Sadid; Khan, Md Harunor Rashid; Islam, Md Shiful (Dhaka University Journal of Biological Sciences, 2021)
Abstract not available Dhaka Univ. J. Biol. Sci. 30(1): 125-131, 2021 (January)